Compromised DNA Repair Promotes the Accumulation of Regulatory T Cells With an Aging-Related Phenotype and Responsiveness - Pieren, Daan K. J.; Smits, Noortje A. M.; Imholz, Sandra; Nagarajah, Bhawani; van Oostrom, Conny T.; Brandt, Renata M. C.; Vermeij, Wilbert P.; Dollé, Martijn E. T.; Guichelaar, Teun (Frontiers in Aging, 2021)
Decline of immune function during aging has in part been ascribed to the accumulation of regulatory T cells (Tregs) and decreased T-cell responses with age. Aside from changes to T cells that occur over a lifetime, the impact of intracellular aging processes such as compromised DNA repair on T cells remains incompletely defined. Here we aimed to define the impact of compromised DNA repair on T-cell phenotype and responsiveness by studying T cells from mice with a deficiency in their DNA excision-repair gene Ercc1. These Ercc1 mutant (Ercc1-/Δ7) mice show accumulation of nuclear DNA damage resulting in accelerated aging. Similarly to wild-type aged mice, Ercc1-/Δ7 mice accumulated Tregs with reduced CD25 and increased PD-1 expression among their naive T cells. Ercc1-deficiency limited the capacity of Tregs, helper T cells, and cytotoxic T cells to proliferate and upregulate CD25 in response to T-cell receptor- and IL-2-mediated stimulation. The recent demonstration that the mammalian target of rapamycin (mTOR) may impair DNA repair lead us to hypothesize that changes induced in the T-cell population by compromised DNA repair may be slowed down or reversed by blocking mTOR with rapamycin. In vivo dietary treatment of Ercc1-/Δ7 mice with rapamycin did not reduce Treg levels, but highly increased the proportion of CD25+ and PD-1+ memory Tregs instead. Our study elucidates that compromised DNA repair promotes the accumulation of Tregs with an aging-related phenotype and causes reduced T-cell responsiveness, which may be independent of mTOR activation.